2006
DOI: 10.1253/circj.70.442
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nifekalant and Lidocaine for the Treatment of Shock-Refractory Ventricular Fibrillation

Abstract: Background Although nifekalant is a class III antiarrhythmic agent without negative inotropic activity, its effect in patients with shock-refractory ventricular fibrillation remains unclear. Methods and ResultsPatients who had an out-of-hospital cardiac arrest with ventricular fibrillation that persisted after 3 shocks from an external defibrillator, intravenous epinephrine, and another shock were retrospectively studied. The patients received lidocaine from January 1997 through June 2001 and nifekalant from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
3
25
0
3
Order By: Relevance
“…6 However, there have been few single center studies regarding the effect of NIF on patients with shock-resistant, out-ofhospital VF. The rate of admission alive to the hospital was 67% (37 survivors of 55 patients treated with NIF), 15 which was comparable with the present results, where the data were collected from 4 established emergency departments. However, over 20 min spent until NIF was administered following the first shock.…”
Section: Nif For Out-of-hospital Cardiac Arrestsupporting
confidence: 90%
“…6 However, there have been few single center studies regarding the effect of NIF on patients with shock-resistant, out-ofhospital VF. The rate of admission alive to the hospital was 67% (37 survivors of 55 patients treated with NIF), 15 which was comparable with the present results, where the data were collected from 4 established emergency departments. However, over 20 min spent until NIF was administered following the first shock.…”
Section: Nif For Out-of-hospital Cardiac Arrestsupporting
confidence: 90%
“…Several studies have demonstrated the efficacy of NIF in arresting or controlling sustained VT/VF. [11][12][13][14][15] NIF is easy to use for the treatment of VT/VF, developing in association with ACS, because of its slight effects on hemodynamic status and the rapid onset of its beneficial effects. Unlike AMD, however, NIF selectively blocks IKr channels and eventually frequently causes QT interval prolongation during sinus rhythm, and might thus give rise to torsade de pointes (TdP) as a proarrhythmic effect.…”
mentioning
confidence: 99%
“…85 Compared with amiodarone, nifekalant hydrochloride has unique pharmacokinetics for rapid action and clearance, and has several advantageous characteristics, particularly for emergency care, including the improvement of the defibrillating threshold and minimal cardiac depressant effect. [86][87][88] In addition to a previous single center experience, 89 the recent multicenter registry study of Japanese Population-based Utstein-style study with basic and advanced Life Support Education (J-PULSE) demonstrated that nifekalant hydrochloride improved the survival rate of hospitalized patients compared with outof-hospital cardiac arrest to more than 70%. 90 Thus, intravenous administration of nifekalant hydrochloride seems to be feasible and can be adjunctive to advanced cardiac life support.…”
Section: Emerging Importance Of Pre-hospital Management For Life Savingmentioning
confidence: 98%